«Red lines» in administration and management of complex systems - Voronin, A.; Savchenko, A. (Проблеми керування та інформатики, 2025)
The problem of optimizing a control system for an object created to fulfill several purposes is considered. Such a system has limited resources, determined during the administration process, based on the real capabilities of the developer. When optimizing the system, it is necessary to take these restrictions into account without violating them. This explains the presence of so-called «red lines», approaching which is undesirable or completely unacceptable. The optimization problem contains optimization arguments that deliver the extremum to the objective function. Розглянуто задачу оптимізації системи керування об’єктом, створеним для кількох цілей. Така система має обмежені ресурси, які визначаються в процесі адміністрування з огляду на реальні можливості розробника. При оптимізації системи необхідно враховувати ці обмеження та не порушувати їх. Цим пояснюється наявність так званих «червоних ліній», наближення до яких є небажаним або зовсім неприпустимим. Задача містить аргументи оптимізації, які забезпечують екстремум цільовій функції.